Perbedaan Kadar Trigliserida Menggunakan Serum dan Plasma Edta dengan Biosystem A15 - Sarah Aminah; Indah Sari; Bastian Bastian (Poltekkes Kemenkes Semarang, 2022)
Trigycerides are the main lipid component in food intake, which is about 98% of total lipids and the remaining 2% consists of phospholipids and cholesterol. Triglycerides are present in adipose tissue, skeletal muscle, liver, lungs, and intestines to Â provide energy in metabolic processes. Who estimates about 1 bilion individuals are overweight and about 300 milion individuals are defined as obese, normal triglyceride levels usually do not exceed 150 mg/dl, if triglyceride levels increase by more than 200 mg/dl then called hypertriglyceridemia. The research aims to determine the difference in triglceride levels using serum and plasma EDTA conducted at the Center For Health Laboratories (BBLK) Palembang. The type of research used is cross Sectional with research designintact group comparison. The sample consisted of 30 serums and 30 plasma EDTA taken from 30 respondents. Research is carried out starting from the preparation of patients, taking examination materials, processing of examination materials, analysis and results of research. The average levels of triglyceride examination using serum and plasma were obtained consecutively at 0.91 mmol/L and 0.83 mmol/L. Mann Whitney test results found that the significant value was p = 0.240. The p value obtained is p>0.05. The results can be concluded that there is no difference in examination of triglyceride levels using serum and plasma EDTA.